Understanding the Experiences of Mothers of Children with Autism Spectrum Disorder in Constructing Family Routines - McAuliffe, Tomomi (Curtin University, 2019)
This thesis explored the experiences of mothers of children with autism spectrum disorder in constructing family routines by comparing their household status and region of residence. The thesis unpacked the complexity involved in mothers’ roles in constructing family routines. Family routines were key in providing mothers with a sense of internal control. Many mothers sacrificed self-care activities to deal with time-pressure; however, mothers were intrinsically motivated to support their families despite the challenges.